Viral Hepatitis in the Canadian Inuit and First Nations Populations - Gerald Y Minuk; J Uhanova (Canadian Journal of Gastroenterology)
OBJECTIVE: To review published prevalence data regarding hepatitis A (HAV), B (HBV) and C (HCV) in Canadian Inuit and First Nations populations.